Implementasi Manajemen Mutu dalam Mengembangkan Kompetensi Peserta Didik di SMA Swasta Muhammadiyah 4 Babalan - Nur Qomarina; Muhammad Rizki Syahputra; Diani Syahfitri (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to examine the implementation of quality management at SMA Swasta Muhammadiyah 4 Babalan and its impact on improving the competence of students. The research method used is a qualitative method with data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques used include data condensation, data presentation, and conclusion drawing and verification. The results showed three main findings. 1) In quality management planning, SMA Swasta Muhammadiyah 4 Babalan conducts customer identification by emphasizing the importance of leaders who understand the needs of internal and external customers for the success of educational programs. 2) The implementation of quality management focuses on customers through periodic meetings with teachers, staff, and parents to evaluate the program and hear feedback related to customer satisfaction. 3) The principal's total involvement in communication and cooperation with stakeholders, including teachers, staff and parents, has been proven to improve the quality of education and learners' competencies. Overall, the implementation of quality management at SMA Swasta Muhammadiyah 4 Babalan has succeeded in creating an educational atmosphere that supports the optimal development of learners' competencies.